Conciliação de medicamentos : fatores de risco, documentação da prática e desenvolvimento de instrumento de avaliação - Silvestre, Carina Carvalho (2018)
Introduction. Medication reconciliation is a process designed to promote communication and teamwork to prevent medication errors at transition of care points. In Brazil studies on the medication reconciliation are still incipient. Aim. To analyze the medication reconciliation under aspects related to risk factors for unintentional discrepancies, documentation of the practice and development of instrument to evaluate the medication reconciliation. Methods. The study was conducted in three stages. The first one was a prospective, case-control study with the aim of identifying the potential risk factors for unintentional medication discrepancies (UMD) at hospital admission. In addition, another study was carried out bringing reflections on the quality of documentation of the history of use of medicines in hospitals and the need for improvements in this process. The second step consisted of a cross-sectional study conducted in a teaching hospital. The clinical notes of nurses, pharmacists and physicians were evaluated to characterize the records on medication use, additionally analysis of communication failures was carried out in all medical records. The last step corresponded to a methodological development study to elaborate and validate the content of a survey questionnaire on the accomplishment of the medication reconciliation in Brazilian hospitals. Results. The findings of the first stage showed that patients submitted to admission procedures after transfers between hospitals were three times more likely to have an UMD compared to patients who were admitted directly from home. In the second stage, it was evidenced that the inefficient communication among the care teams may have been the primary cause of the findings of the previous study. Regarding the evaluation of written documentation, there were no reports of allergies and adverse drug reactions in 44 (21.9%) of nurses, 8 (22.9%) of pharmacists and 54 (26.8%) of physician’s clinical notes. In addition, 1,588 changes in prescriptions were identified in the data collection period, where only 390 (24.5%) of these changes were justified. Furthermore, it was possible to identify 485 communication failures on medications in 65.3% (n = 132) of the evolutions evaluated. In relation to the development of the questionnaire, three preliminary versions were elaborated. The third version was submitted to the content validation process through Delphi resulting in the final version of the questionnaire with 17 questions. Conclusion. Inefficient communication, especially on medication, among the various actors in the care team can greatly influence the achievement of drug reconciliation and hence patient safety in the care transition.